Experimental approach of the prosodic component in the linguistic input of gardenpath sentences in Brazilian Portuguese - Fonseca, A. A. (Journal of Speech Sciences, 2021)
This study investigates what part the prosodic component plays in linguistic processing. Can prosodic cues be computed early in the linguistic process and influence the syntactic processing? Some studies in American English (Kjelgaard&Speer, 1999; DeDe 2010) and German (Steinhaueret al 1999) have shown that yes, furthermore, prosodic elements like intonational phrases can modify the syntactic chain during processing. Our work is based on the premises that, during the perceptive processing, an early activation of the prosodic component in the linguistic input can lead the sentence’s syntactic structure.There have been studies in Brazilian Portuguese that show how prosody influences parsing (Lourenço-Gomes 2008; Magalhães& Maia 2006), however, none that tested the effects of prosodic constituents’ organization in online tasks.